2010
DOI: 10.9755/ejfa.v22i1.4902
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses in growth and water relationship of<br>Medicago sativa (L.) cv. Gabès and Astragalus gombiformis (Pom.)<br>under water-limited conditions

Abstract: Abstract:This study aims to compare the growth attributes and water relationship of two-forage legume plants: a crop plant, Medicago sativa (L.) cv. Gabès, and a wild plant, Astragalus gombiformis (Pom.), under drought-stress conditions. Water deficit stress was imposed at 40% and 70% of field capacity (FC) from 60 to 90 days after sowing, while the control pots were maintained at 100% FC throughout the period of entire growth. The results showed that the high potentialities of growth in both species were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
1
20
1
2
Order By: Relevance
“…However, in this experiment, as the plants received low water volume, the stems grew faster. These results were contrary to those of the studies from Gorai et al (2010) and Shao et al (2008), which suggested that water deficit caused height reduction in stressed plants. This may suggest that different species have different responses to water stress.…”
Section: Effect Of Water Stress On Morphological Performancescontrasting
confidence: 99%
“…However, in this experiment, as the plants received low water volume, the stems grew faster. These results were contrary to those of the studies from Gorai et al (2010) and Shao et al (2008), which suggested that water deficit caused height reduction in stressed plants. This may suggest that different species have different responses to water stress.…”
Section: Effect Of Water Stress On Morphological Performancescontrasting
confidence: 99%
“…Plants under water deficit show decreased stem elongation [47] and restricted formation and number of leaves due to increased leaf senescence [48]. To help prevent water loss under stressful conditions some plants secrete and accumulate waxes in the surface of the leaves [49].…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have observed that WUE declines under water stress conditions and sustained that the species employed a water-use strategy (Hu et al, 2006;Gorai et al, 2010). Blum (2005) considered lower WUE as an avoidance strategy.…”
Section: Discussionmentioning
confidence: 99%
“…First, according to Wu et al (2008), WUE decrease may be attributed to a low biomass production under severe water deficit conditions. Secondly, Gorai et al (2010) sustained that WUE reduction under drought is due to an optimal water use by plants. Thirdly, Moreno et al (2008) claimed that this behavior is caused by the predominance of non stomatal limitation to photosynthesis and by the fact that stomata are less sensitive to water deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation